“In biology nothing makes sense unless in the light of Evolution”. Theological Incorporation of this Biological Principle - Florio, Lucio (Teología, 2018)
The article aims to investigate some common ground between formal theology and biological evolution. Assuming both the absence of a basic conflict and acknowledging the possibility not only of dialogue but also of an integration of evolutionary issues within formal theology, it will seek to identify some tasks within the theological disciplines while searching for a critical assimilation of evolution. If theological reflection is an insight into faith through the rational resources available, life will have to be thought of as a creature in the current paradigm in order to understand it rationally. Such paradigm today is that of evolution. However, the invitation to an active assimilation exercise within the intellectus fidei seems not to have found a theological reception consistent with the various theological disciplines as yet. The apparent state of peace and acceptance of the evolutionary core by formal education leads to a complex and challenging task: that of incorporating an evolutionary panorama within theological reflection.